Measurement of semivolatile carbonaceous aerosols and its implications: A review - Y. Cheng; K.B. He; F.K. Duan; M* Zheng; Y.L. Ma; J.H. Tan (Environment International, 2009)
Measurement of carbonaceous aerosols is complicated by positive and negative artifacts. An organic denuder with high efficiency for removing gaseous organics is an effective approach to eliminate the positive artifact, and it is a precondition for the accurate determination of SVOC by an adsorbent backup filter. Evaluations of different configurations of the organic denuder, and SVOC determined by different denuder-based samplers, both integrated and semi-continuous, are reviewed. A new equation for determination of the denuder efficiency is estimated, considering the efficiency of removing both the gaseous organics that could be adsorbed by the quartz and the gaseous passing through the quartz that could be subsequently adsorbed by the backup adsorbent filter. The origin of OC on the backup quartz filter, behind either quartz or Teflon filter, is quantitatively evaluated by the denuder-based method based on the data published. The backup-OC is shown to be dominated by either gaseous organics passing through the front filter or the evaporated particulate organic carbon depending on the sampling environment.
Keywords: Carbonaceous aerosol